Analysis of single-diode and improvement of double-diode photovoltaic source modelling methods and techniques - Shongwe, Samkeliso Hubert (Department of Electrical Engineering, 2023)
Modelling of photovoltaic systems is essential for designers of solar generation plants to do a yield analysis that accurately predicts the expected power output under changing environmental conditions. There are a few different models which are used and they all differ in their implementation and also on the accuracy. The main aim of this thesis is to analyse different PV modelling methods which are based on the single-diode and double-diode models. The study carried out, falls under two sections. The first study was to figure out which single-diode model produces the most accurate results. The second study is extended to double-diode models. Here, the thesis goes on to propose a different PV modelling method which is based on the double-diode representation of a PV module that will be verified and compared with other models and experimental data. An analysis of the various different single-diode models is done based on two commercially available PV modules: SQ80 and the KC200GT, in which the simulated results are compared with the characteristics extracted from the datasheets. Parameter estimation techniques within a modelling method are generally used to estimate the five unknown parameters in the single-diode model. Two sets of estimated parameters were used to plot the I-V characteristics of two PV modules, SQ80 and KC200GT, for the different sets of modelling equations which are classified into models 1 to 5 in this study. Each model is based on the different combinations of diode saturation current and photo generated current, plotted under varying irradiance and temperature. Modelling was done using Matlab/Simulink software and the results from each model were first verified for correctness against the results produced by their respective authors, then a comparison was made amongst the different models (models 1 to 5) with respect to experimentally measured and datasheet I-V curves. The SQ80 module is also connected in the lab and experimental values are measured from it under different environmental conditions. A comparison is then made using the different modelling methods with the experimental data to evaluate the accuracy of the models. In the second study, the new proposed double-diode PV modelling method is also implemented using datasheet information for three commercial PV modules made from different technologies: mono-crystalline, poly-crystalline and thin-film technology. This method is an improvement on an existing method and is more accurate. A comparison is made with the characteristics extracted from the datasheet to verify that it produces accurate results. A comparison of this modelling method is also made with the experimentally measured data from the SQ80 PV module. The results obtained were used to draw conclusions on which combination of parameter extraction and modelling method best emulates the manufacturer's characteristics.